Essays in macroeconomics: Inflation inequality, consumption baskets and impulse responses - Christoffer Jessen Weissert (University of Copenhagen, Department of Economics, 2022)
The dissertation consists of three self-contained chapters on topics within macroeconomics. All chapters share an orientation towards empirical analysis of macroeconomic questions. New methods for empirical analysis are presented in the first and third chapter. The method presented in the first chapter contributes to analyses of inflation inequality. The method presented in the third chapter contributes to analyses on how the economy responds to shocks. The inflation inequality discussed in the first chapter relates to households' consumption behavior. In the first and second chapter specific empirical analyses on US households' consumption behavior is conducted.
Keywords: 330